Performance of coffee cultivard in organic cultivation system in Tropical Semideciduous Forest Region in Minas Gerais - Moura, Waldênia de Melo; Lima, Paulo César de; Fazuoli, Luiz Carlos; Condé, Aurinelza Teixeira Batista; Silva, Tales Campos da (Coffee Science - ISSN 1984-3909, 2014)
The objective for this work was to evaluate the behavior coffee of cultivars under organic cultivation system, in order to indicate which are more adapted to tropical semideciduous forest region in Minas Gerais (Zona da Mata Mineira). The experiments were conducted from 2003 to 2009, in a randomized block design with thirty genotypes (cultivars and lines) and three replicates, in “Araponga”, “Espera Feliz” and “Tombos” municipalities. Participative methodology of research was used and the evaluations started in 2006 and lasted four harvesting. The cultivars presented variability for most of the evaluated characteristics. In general, it was found low incidence of diseases and pests. The vegetative vigor, yield, severity of the coffee leaf rust and brown eye spot were significantly influenced by the growth areas. For each cultivar it was identified a growth area where the agronomic behaviour was best, including cultivars classified as resistant, moderately resistant and suceptible to leaf rust. Sabiá 708, Catucaí Amarelo 24/137, IBC Palma 1, Paraíso MG H 419-1, Catucaí Vermelho 36/6, Catuaí Vermelho IAC 15, Oeiras MG 6851 cultivars and the line H518 were the most indicated to the organic cultivation system in Zona da Mata Mineira.